The relationship between constitutional alignment and varus osteoarthritis of the knee - Vandekerckhove, Pieter-Jan T. K.; Matlovich, Nicholas; Teeter, Matthew G.; MacDonald, Steven J.; Howard, James L.; Lanting, Brent A. (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2017)
Purpose The role of neutral alignment in total knee arthroplasty (TKA) on short- and long-term outcomes has become controversial. Based on the concept of constitutional varus, it has been suggested that under-correction in TKA in a varus osteoarthritis (OA) population might lead to better clinical outcomes. However, it is still unknown what the relationship between constitutional varus and the development of end-stage OA is. The goal of this study was to analyse the contribution of constitutional varus in a medial OA population and to define a correlation between the constitutional alignment and end-stage varus OA. Methods Based on full-length radiographs, corrected for the intra-articular deformity of the knee, of 315 patients with unilateral end-stage medial OA of the knee (Charnley type A), a correlation in the coronal plane was made between medial end-stage OA and the contralateral non-arthritic side. Results With increasing varus alignment in the arthritic limb, the physiologic limb alignment also became more varus. The proportion of constitutional varus rose with increasing overall alignment and was found to be continuous for males. Constitutional varus was three times higher in men when the overall arthritic alignment was greater more than 6° varus. Conclusion Constitutional varus significantly contributes to varus osteoarthritis and was found to be higher than in the general population. Level of evidence III.